La concentración de la intermediación y la congestión vehicular en zonas metropolitanas de México - Pichardo Corpus, Juan Antonio (El Colegio de México A.C., 2024)
This article explores the relationship between congestion and the betweenness concentration of street networks in Mexican metropolitan areas. The analysis shows that the size of the network and its quasi-planarity determine the edges' proportion, which concentrates most of the network betweenness. This edge proportion explains 50 and 70% of the variation in the number of hours lost due to congestion. The results indicate that it is almost impossible to significantly reduce congestion levels by widening streets and creating bridges or overpasses. This implication strengthens the proposals to invest in mass transit, alternative means to motorized transport, and to develop cities with a mix of land uses that avoid long commutes.